2019
DOI: 10.1587/elex.16.20181135
|View full text |Cite
|
Sign up to set email alerts
|

SiC trench MOSFET with integrated side-wall Schottky barrier diode having P<sup>+</sup> electric field shield

Abstract: A new SiC trench MOSFET (T-MOSFET) integrated with a side-wall Schottky Barrier Diode (SBD) to form a compact power device is proposed. The proposed structure applies two trenches to form the n-channel and SBD in a single cell, respectively. A P + is implanted after etching the trenches to form a shield for both the gate oxide and the Schottky barrier. The breakdown voltage of the proposed one is about 363% larger than that of the conventional trench MOSFET (CT-MOSFET) with integrated SBD. The integrated SBD o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Trench SiC power MOSFETs, due to their relatively complex process, may not have the cost advantage of planar SiC power MOSFETs [31]. Integrating an external Schottky diode may exacerbate this cost disadvantage, eroding the benefits provided by the smaller cell pitch of trench SiC power MOSFETs [32]. Furthermore, there are variations in the characteristics of P-type implants among different vendors and even different generations of trench SiC power MOSFETs from the same vendor, making the research on the reliability of the body diode in SiC power MOSFETs essential.…”
Section: Introductionmentioning
confidence: 99%
“…Trench SiC power MOSFETs, due to their relatively complex process, may not have the cost advantage of planar SiC power MOSFETs [31]. Integrating an external Schottky diode may exacerbate this cost disadvantage, eroding the benefits provided by the smaller cell pitch of trench SiC power MOSFETs [32]. Furthermore, there are variations in the characteristics of P-type implants among different vendors and even different generations of trench SiC power MOSFETs from the same vendor, making the research on the reliability of the body diode in SiC power MOSFETs essential.…”
Section: Introductionmentioning
confidence: 99%
“…In [8][9][10][11], it was reported that SBD was integrated by splitting the P-base or gate of power MOSFET, of which the performance degenerates resulting from the cell pitch increases. Yi et al [12] proposed a float P+-shield region (PSR) trench MOSFET with integrated SBD but the floating PSR will introduce reliability problems [13]. Kobayashi et al [14] proposed a SWITCH-MOS with integrated sidewall SBD.…”
Section: Introductionmentioning
confidence: 99%
“…In [8][9][10][11], it was reported that SBD was integrated by splitting the P-base or gate of power MOSFET, of which the performance degenerates resulting from the cell pitch increases. Yi et al [12] proposed a float P+-shield region (PSR) trench MOSFET with integrated SBD but the floating PSR will introduce reliability problems [13]. Kobayashi et al This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations